Reflection of Character Values in English Textbook Entitled Pathway to English for SMA/MA Grade X - Salsabila Salsabila; Rina Listia; Fahmi Hidayat; Fatchul Mu’in (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
The problems of this research are focused on whether the character values are found in the English textbook or not and how they are reflected. This research analyzes all chapters in the English textbook entitled Pathway to English for SMA/MA Grade X, specifically the reading texts. The approach of this research is qualitative research. In collecting the data, two types of instruments are used which are the researcher herself and the data sheet. The result of this research showed that there are 18 character values reflected in this textbook covering all of them. Appreciation was represented 16 times in the reading texts, being the highest value of all. To reflect appreciation value in teaching and learning process, one of the ways that teachers can do to integrate it is they can motivate the students to produce something useful for themselves as well as society or give rewards to the students who do their jobs well. It can be concluded that this English textbook is ideal as a teaching material for developing character values of students because it contains all 18 character values that the 2013 Curriculum suggests should be included in the textbook. Knowing that the Ministry of Education and Culture requires English textbook for Senior High School to include at least eight values, this book shows that an ideal English textbook exists. Keywords: Character Values, Textbook Analysis, English textbook, reading texts